Phenolic compounds and antioxidant activity in tetraploid wheat - Delvecchio L.N.; Taranto F.; Mangini G.; Blanco A.; Pasqualone A. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Phenolic compounds have been widely studied for their health value, as they exert a protective role against chronic degenerative diseases, mainly due to their antioxidant properties. Cereals are at the basis of the food pyramid and, even if they are not one of the main sources of phenolic compounds, they can effectively contribute to the dietary uptake of these secondary metabolites. After an overview of functions and mechanisms of bioavailability, the extraction methods and varietal variability of phenolic compounds in tetraploid wheat are reviewed, in comparison with bread wheat. The quantitative distribution of the various fractions and classes of phenolic compounds in the caryopsis are discussed, with special attention to ferulic acid. The state of the art about the production of phenolic extracts from bran is reviewed, pointing out the most recent technologies adopted to recover the insoluble-bound phenolic fraction.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)